Effect of laser parameters on surface roughness of laser modified tool steel after thermal cyclic loading - Sheng, Annie Lau; I., Ismail; S. N., Aqida (IOP Publishing, 2018)
This study presents the effects of laser parameters on the surface roughness of laser modified tool steel after thermal cyclic loading. Pulse mode Nd:YAG laser was used to perform the laser surface modification process on AISI H13 tool steel samples. Samples were then treated with thermal cyclic loading experiments which involved alternate immersion in molten aluminium (800°C) and water (27°C) for 553 cycles. A full factorial design of experiment (DOE) was developed to perform the investigation. Factors for the DOE are the laser parameter namely overlap rate (η), pulse repetition frequency (f PRF) and peak power (Ppeak ) while the response is the surface roughness after thermal cyclic loading. Results indicate the surface roughness of the laser modified surface after thermal cyclic loading is significantly affected by laser parameter settings.